P06.14 The effect of sexual intercourse on vaginal colonisation with candida. (13th September 2015) - Watson, CJ; Fairley, CK; Garland, SM; Myers, S; Pirotta, M
Abstract : Introduction: Recurrent vulvovaginal candidiasis (RVVC) results in significant physical, financial and psychological sequelae for women, and many women report that VVC affects their intimate relationships. The aetiology of RVVC remains uncertain, and some studies suggest sexual intercourse may be responsible for transmission of Candida species. No publications have documented the affect of sexual intercourse on vaginal candida colonisation. Methods: Fifty nine participants who were culture positive for Candida spp. at screening took part in a randomised controlled trial investigating the effect of oral garlic and placebo on vaginal candidal colonisation. Participants self-collected daily vaginal swabs during the two weeks before menstruation. They kept a daily diary and recorded incidence of sexual intercourse and abnormal vaginal symptoms. Swabs were analysed for quantitative colony counts of candida before and after sexual intercourse. Results: There were 149 episodes of sexual intercourse in participants reporting sexual activity (n = 38) over the two week study period. Colonisation levels rose the day following sexual intercourse in 51 episodes, and fell in 56 episodes. In 42 episodes of sexual intercourse, the levels remained the same or women were culture negative on the day following and two days following sexual intercourse. On fifty occasions women had symptoms (itch, abnormal vaginal discharge) on the day of sexual intercourse, and 41 women reported abnormal symptoms two days after sexual intercourse. In 75 episodes, there were no abnormal symptoms the day of, or the day following sexual intercourse. Conclusion: In this study, sexual intercourse, colonisation levels and abnormal vaginal symptoms appeared to be unrelated. Further investigation is recommended into dyspareunia and abnormal vaginal symptoms following sexual intercourse experienced by women with RVVC. Disclosure of interest statement: No pharmaceutical grants were received in the development of this study.